CD19 CAR-T cell therapy: a new dawn for autoimmune rheumatic diseases? - Rangel-Peláez, Carlos; Martínez-Gutiérrez, Laura; Tristán-Manzano, María; Callejas, José Luis; Ortego-Centeno, Norberto; Martín, Francisco; Martín, Javier (Frontiers in Immunology, 2024)
Autoimmune rheumatic diseases (ARDs), such as rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis, involve dysregulated immune responses causing chronic inflammation and tissue damage. Despite advancements in clinical management, many patients do not respond to current treatments, which often show limited efficacy due to the persistence of autoreactive B cells. Chimeric antigen receptor (CAR)-T cell therapy, which has shown success in oncology for B cell malignancies, targets specific antigens and involves the adoptive transfer of genetically engineered T cells. CD19 CAR-T cells, in particular, have shown promise in depleting circulating B cells and achieving clinical remission. This review discusses the potential of CD19 CAR-T cells in ARDs, highlighting clinical achievements and addressing key considerations such as optimal target cell populations, CAR construct design, acceptable toxicities, and the potential for lasting immune reset, crucial for the safe and effective adoption of CAR-T cell therapy in autoimmune treatments.